2012
DOI: 10.1037/a0024394
|View full text |Cite
|
Sign up to set email alerts
|

Emerging opportunities for psychologists: Joining consumers in the recovery-oriented care movement.

Abstract: A transformation is occurring in mental health services throughout the country that presents opportunities for both seasoned and aspiring psychologists. This paper draws on the experiences of (a) a VA staff psychologist, (b) a psychology postdoctoral fellow, (c) a director of clinical training (and clinicalcommunity psychologist) at an APA-accredited doctoral training program, and (d) a psychologist who leads the Psychosocial Rehabilitation and Recovery Section of the Department of Veterans Affairs' Office of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Some of the earliest works on recovery were written by pioneers who have firsthand experience of mental illness (Coleman, 1999;Deegan, 1988;O'Hagan, 1996) and these captured the attention of those outside the field, such as academics and policymakers. In Hong Kong, unlike western countries (Cohen et al, 2012;Jacobson & Curtis, 2000), the notion of recovery remains predominantly promoted and interpreted by health professionals or academics, suggesting that a distinctive figure or a strong voice from the users' community has yet to be found in Hong Kong: someone who could act as an advocate for those affected by mental illness. This implies that health professionals as well as academics should tread steadily but also lightly in this emerging recovery movement in Hong Kong, so as not to drown out the voices of service users (Tse, Cheung, Kan, Ng, & Yau, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some of the earliest works on recovery were written by pioneers who have firsthand experience of mental illness (Coleman, 1999;Deegan, 1988;O'Hagan, 1996) and these captured the attention of those outside the field, such as academics and policymakers. In Hong Kong, unlike western countries (Cohen et al, 2012;Jacobson & Curtis, 2000), the notion of recovery remains predominantly promoted and interpreted by health professionals or academics, suggesting that a distinctive figure or a strong voice from the users' community has yet to be found in Hong Kong: someone who could act as an advocate for those affected by mental illness. This implies that health professionals as well as academics should tread steadily but also lightly in this emerging recovery movement in Hong Kong, so as not to drown out the voices of service users (Tse, Cheung, Kan, Ng, & Yau, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Most of the literature that reviews recovery movements originates from the US or the UK (Cohen, Abraham, Burk, & Stein, 2012;Myers, 2010;Slade, Adams, & O'Hagan, 2012). Some of the earliest works on recovery were written by pioneers who have firsthand experience of mental illness (Coleman, 1999;Deegan, 1988;O'Hagan, 1996) and these captured the attention of those outside the field, such as academics and policymakers.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that there have been some changes in the discourse and presence of recovery-oriented services within the mental health system (Anthony, 1993; Bailey, 1997; Blanch, Fischer, Tucker, Walsh, & Chassman, 1993; Clarke, Oades, & Crowe, 2012; Cohen, Abraham, Burk, & Stein, 2012; Davidson & Roe, 2007; Mead & Copeland, 2000). Such a paradigm shift was largely influenced by the consumer movement’s increasing presence and voice within the mental health system, including more paid positions for patient-advocates and peer supporters in hospitals and community mental health agencies.…”
Section: Discussionmentioning
confidence: 99%
“…One epidemiological study reported that only 15% of all individuals with SMI were receiving minimally adequate treatment (Wang, Demler, & Kessler, 2002). As such, it has increasingly been recognized that psychology trainees and psychologists require specialized training to provide adequate treatment for those with SMI (Carr, Bhagwat, Miller, & Ponce, 2014; Chu et al, 2012; Cohen, Abraham, Burk, & Stein, 2012; Corrigan, Steiner, McCracken, Blaser, & Barr, 2001; Hargrove, 1990; Hoge, Stayner, & Davidson, 2000; Lefley, 1990; Miller, Carr, Utter, Styron, & Steiner, 2017; Mueser, Silverstein, & Farkas, 2013; Roe, Yanos, & Lysaker, 2006). To bridge this gap, in 2014 the APA released a free curriculum for psychologists and other mental health professionals working with individuals with SMI (APA & Jansen, 2014).…”
Section: The Need For Specialized Postdoctoral Psychology Training In...mentioning
confidence: 99%